2019
DOI: 10.1136/archdischild-2018-316231
|View full text |Cite
|
Sign up to set email alerts
|

Association between hypotension and serious illness in the emergency department: an observational study

Abstract: BackgroundThe value of routine blood pressure measurement in the emergency department (ED) is unclear.ObjectiveTo determine the association between hypotension in addition to tachycardia and the Shock Index for serious illness.DesignObservational study.SettingUniversity ED (2009–2016).Participants, methods and main outcomesRoutine data collected from consecutive children <16 years. Using logistic regression, we assessed the association between hypotension (adjusted for tachycardia) and Shock Index (ratio heart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…5 7 8 10-14 32 33 In our previous single-centre study, we found an association of high Shock Index for hospital and ICU admission in children with different presentations at the ED. 14 Although this previous study included both febrile and non-febrile children, our study confirms an association of high Shock Index with SBI, ILSI and ICU admission in febrile children.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…5 7 8 10-14 32 33 In our previous single-centre study, we found an association of high Shock Index for hospital and ICU admission in children with different presentations at the ED. 14 Although this previous study included both febrile and non-febrile children, our study confirms an association of high Shock Index with SBI, ILSI and ICU admission in febrile children.…”
Section: Discussionsupporting
confidence: 77%
“…6 In paediatrics, evidence of the Shock Index is limited to children with trauma, [7][8][9][10] children with septic shock [11][12][13] and a single-centre general ED population. 14 To our knowledge, the Shock Index as a potential non-invasive measure in the early assessment for recognition of serious illness, including need for immediate life-saving interventions (ILSIs) and SBI, has not yet been evaluated. In addition, the association of the Shock Index with ICU admission in febrile children in a multicentre cohort is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In our cohort, BP was by far the most commonly missed parameter, and similarly low rates of BP measurement in the paediatric ED have been reported consistently in the previous research. [38][39][40] This affects the development of scoring systems that include BP, as they are using cohorts with significant amounts of missing data. Furthermore, the 'real-world' performance of a score may be greatly affected if one parameter is consistently not measured, reducing opportunities for the reliable detection of serious illness.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is that blood pressure, cyanosis and diminished urine output were not included in the data collection. A previous study showed that, although hypotension is associated with serious illness in children, its sensitivity is limited as routine measurement in all children attending the ED42 43 and it is a late sign in children with sepsis in comparison with adults. On the other hand, in adolescents, similar to adults, hypotension might present earlier in the disease course and thus including blood pressure could provide valuable information.…”
Section: Discussionmentioning
confidence: 99%